TRAFFIC MANAGEMENT ANALYSIS OF THE MANGGARAI STATION AREA ROAD NETWORK - Sari, Christina; Rintawati, Dewi (International Journal on Livable Space, 2022)
The Manggarai Station area has an urban function as a residential area which resulted in a very high movement within the region. Manggarai Station is one of the busiest stations and one with the most varied transportation hub, i.e., intermodal railway, TransJakarta, and Airport Trains in Jabodetabek. Manggarai Station is located in the residential area whose existing condition needs to be managed in the form of arrangement of vehicle parking queues with several access to and from the Manggarai station. Vehichle queues at the Manggarai station area are mostly caused by KRL transit passengers who need to change the modes of transportation but with unavailability of waiting areas. This study aims to identify and formulate the inventory problems-conflicts at intersection traffic and evaluate the performance of intersections and road-sections on the road networking at the Manggarai Region. The analytical method was used and based on the 1997 Indonesian Road Capacity Manual. The results of the analysis of the intersection's performance in the existing conditions have a delay of 32 seconds/vehicle and an average road speed of 21.5 km/hour. With the implementation of the transit hub construction recommendation and arrangement of the pelican crossing, the speed increases to 30.5 km/hour. Therefore, in the short term, the traffic engineering management recommendation can be applied to solve the problem of congestion and road user accessibility.   Keywords: Traffic Management, Station Area, VCR Ratio